Research and development: financial constraints and the role of public funding for small and medium-sized enterprises - Dirk Czarnitzki (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2002)
This paper presents microeconometric evidence on financing con-traints for research and development activities in German small and medium?sized firms (SME). Special attention is paid to the role of public R&D subsidies. For this purpose SME in Western and East-ern Germany are compared because these regions are very different in their supply of public R&D funding. It turns out that Western German SME are financially constrained in their R&D activities by both internal and external resources. In Eastern Germany, firms are not sensitive to external constraints, possibly due to high public R&D subsidies. The results suggest that R&D in Eastern Germany is to a large extent driven by public subsidies since the German re?unification in 1990 and that the usual financial market mechanisms are repealed with respect to R&D in this region.
Keywords: O38; O31; C24; 330; Research and development; financial constraints; public funding; SME; censored regression models; Industrielle Forschung; Forschungsfinanzierung; Verschuldungsrestriktion; Klein- und Mittelunternehmen; Forschungssubvention; Schätzung; Alte Bundesländer; Neue Bundesländer; Deutschland